2003
DOI: 10.1029/2002jd002710
|View full text |Cite
|
Sign up to set email alerts
|

Lidar observations of equatorial cirrus clouds at Mahé Seychelles

Abstract: [1] In February-March 1999, nocturnal observations with a ground-based backscatter/ depolarization lidar were conducted during the Airborne Platform for Earth ObservationThird European Stratospheric Experiment on Ozone (APE-THESEO) campaign at Mahé, Seychelles (4.4°S, 55.3°E). Upper tropospheric cirrus clouds were a common feature in the lidar echoes; they were detected for about 67 hours out of a total measurement time of 125 hours. Optical and geometrical characteristics of the clouds detected at altitudes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 47 publications
3
20
0
3
Order By: Relevance
“…8b, the standard deviations are significantly large. A similar relation between cloud optical depth and geometrical depth (physical depth) has been reported by various other investigators for tropical cirrus (Pace et al, 2003;Thomas et al, 2002) and mid-latitude cirrus (Sassen and Cho, 1992).…”
Section: Mean Properties Of Cirrus Clouds In Different Nights and Thesupporting
confidence: 54%
See 1 more Smart Citation
“…8b, the standard deviations are significantly large. A similar relation between cloud optical depth and geometrical depth (physical depth) has been reported by various other investigators for tropical cirrus (Pace et al, 2003;Thomas et al, 2002) and mid-latitude cirrus (Sassen and Cho, 1992).…”
Section: Mean Properties Of Cirrus Clouds In Different Nights and Thesupporting
confidence: 54%
“…In this figure corresponding parameters are plotted with a time resolution of 250 s for 80 nights, in which continuous observations were available for more than 4 h. This plot shows that for low values of τ c (<0.01) the asymmetry is less than 2% and increases nonlinearly with an increase in τ c , indicating that most of the sub-visual cirrus are symmetric. Studies conducted at Mahe Island (4.4 • S, 55.3 • E) also showed (Pace et al, 2003) that in most of the cases the observed cirrus is symmetric. They attributed the low values of ξ mainly to ice precipitation, leading to the accumulation of ice mass near the cloud base.…”
Section: Interdependence Of Cirrus Propertiesmentioning
confidence: 98%
“…Recent studies have focused on the western Pacific warm pool [ Platt et al , 1998, 2002; Heymsfield et al , 1998; Sassen et al , 2000; Comstock et al , 2002]. Other lidar statistics of cirrus cloud properties in the tropics are available only for the Seychelles [ Pace et al , 2003] and eastern India [ Sunilkumar and Parameswaran , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…High tropical cirrus were first reported by Uthe and Russell (1976) who observed cirrus clouds between 12 and 18 km, from the ground lidar station at Kwajalein (8.7 • N, 167.7 • E). Since then, a molteplicity of lidar studies characterized cirrus morphology, often in conjunction with other remote sensing instruments as infrared radiometers or millimeter radars (Platt et al, 1998;Comstock and Sassen, 2001;Wang et al, 2001;Pace et al, 2003;Immler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%